Profil Objek Wisata Pantai Lumintang Di Desa Bentenan Kecamatan Pusomaen Kabupaten Minahasa Tenggara - Mamonto, Dessi Vriska; Maweikere, Audrey Julia Maria; Talumingan, Celcius (Sam Ratulangi University, 2024)
The study aimed to determine the profile of Lumintang Beach tourist attraction in Bentenan Village, Pusomaen District, Southeast Minahasa Regency. The research lasted for two months with research time from June to July 2023. The research was conducted at Lumintang Beach tourist attraction located in the Bentenan Village Tourism Area, Pusomaen District, Southeast Minahasa Regency. The data sources used in this research are primary data and secondary data. Primary data was obtained through direct interviews with processors. Secondary data were obtained from agencies related to the research, literature or previous research. The method used in sampling is purposive sampling, namely samples taken deliberately and the sample is the tourist attraction officer. The analysis technique used is descriptive. The results showed that the Lumintang Beach tourist attraction in Bentenan Village, Pusomaen District, Southeast Minahasa Regency is a tourist spot that has potential and destinations that can be an attraction for visitors by using existing facilities such as boats to visit the islands around Lumintang Beach, jetski and banana boat for visitors to use to play on the water and gazebo visitors can use as a place to relax or carry out thanksgiving events, to support the economy of the Bentenan Village community, the community can make a culinary place as a livelihood.